PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN BUKU PELAJARAN SEKOLAH PADA TOKO BUKU BUMIMEDIA DI DEPOK - Candida Karim, Tanika; Senen (Journal of Research and Publication Innovation, 2024)
This research aims to find out how much influence price has on the decision to purchase school textbooks at the Bumimedia Bookstore in Depok, to find out how much influence product quality has on the decision to purchase school textbooks at the Bumimedia Bookstore in Depok, to find out how much influence price and quality have. Products on the Decision to Purchase School Textbooks at the Bumimedia Bookstore in Depok. This research uses a quantitative approach with a research sample of 83 respondents and a probability sampling technique, as well as a data collection technique through distributing questionnaires. The data analysis methods used are data instrument tests, classical assumption tests, simple and multiple linear regression tests, coefficient of determination and hypothesis testing. The research results show that price (X1) and product quality (X2) have a significant effect on purchasing decisions (Y) with the regression equation Y = 12.338 + 0.382 X1 + 0.324X2. The correlation value is 0.604, meaning that the independent variable and the dependent variable have a strong level of relationship. The coefficient of determination value is 34.9% while the remaining 65.1% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (22,965 > 3.11). This H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence of price and product quality on the decision to purchase school textbooks at the Bumimedia Bookstore in Depok.